2017
DOI: 10.1242/jcs.203034
|View full text |Cite
|
Sign up to set email alerts
|

DNA-dependent protein kinase plays a central role in transformation of breast epithelial cells following alkylation damage

Abstract: DNA alkylating agents form the first line of cancer chemotherapy. They not only kill cells but also behave as potential carcinogens. MNU, a DNA methylating agent, is well known to induce mammary tumours in rodents. However, the mechanism of tumorigenesis is not well understood. Our study reports a novel role played by DNA-dependent protein kinase (DNA-PK) in methylation damage-induced transformation using three-dimensional breast acinar cultures. Here, we report that exposure of breast epithelial cells to MNU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 68 publications
2
21
0
Order By: Relevance
“…Our findings suggested that DNA-PKcs played an important role in cSCC progression because DNA-PKcs promoted cSCC cell migration and invasion. Moreover, similar to the findings of L. Anandi,26 DNA-PKcs expression in the human cSCC SCL-1 cell line was correlated with EMT, indicating that DNA-PKcs facilitates EMT and participates in the processes of cSCC progression and metastasis. This finding is supported by the observation that DNA-PKcs deficiency decreased SCL-1 cell migration and invasion in vitro.…”
Section: Discussionsupporting
confidence: 84%
“…Our findings suggested that DNA-PKcs played an important role in cSCC progression because DNA-PKcs promoted cSCC cell migration and invasion. Moreover, similar to the findings of L. Anandi,26 DNA-PKcs expression in the human cSCC SCL-1 cell line was correlated with EMT, indicating that DNA-PKcs facilitates EMT and participates in the processes of cSCC progression and metastasis. This finding is supported by the observation that DNA-PKcs deficiency decreased SCL-1 cell migration and invasion in vitro.…”
Section: Discussionsupporting
confidence: 84%
“…This result was in concordance with the data collected by van de Vijver et al [32] and Sotiriou et al [33]. Our study illustrates for the first time the role of DNA-PK in breast tumorigenesis [15]. In our study, MNU was used to induce DNA-damage, which in turn resulted in activation of DNA-PKcs which eventually resulted in transformation of non-tumorigenic breast epithelial cells.…”
Section: Short Communicationsupporting
confidence: 93%
“…This report also claimed that tumor formation was independent of the H-ras mutation initially identified by Zarbl et al [7] Given the extent of exposure to DNA damaging agents in everyday life, and lack of knowledge about the precise mechanism of tumorigenesis following DNA damage; the study of the mechanism of DNA damage induced transformation becomes imperative. In a recent study, using the 3-dimensional breast acinar model, we demonstrated that alkylation damage induced cellular transformation, which was mediated via the activation of DNA-PK, a protein involved in the DNA repair process [15]. DNA-PK has been demonstrated in various studies to have diverse functions [16].…”
Section: Short Communicationmentioning
confidence: 98%
“…Previous studies have shown that MNU induces epithelial-mesenchymal transition (EMT)-like phenotype changes in ocular and breast epithelial cells. 97,98 These changes are mediated by methylation damage-induced activation of DNA-dependent protein kinase (DNA-PK). 99 EMT is central to fibrotic posterior capsule opacification in cases of anterior subcapsular cataract and posterior polar cataract.…”
Section: Discussionmentioning
confidence: 99%